Surveillance of Infectious Diseases - Noah, Norman (Encyclopedia of Virology, 2021)
Surveillance is the backbone of any disease control program. Data must be representative, timely, and consistent. Collection of data must be systematic. Analysis of data should include analysis by time, place, and person. Data sources can be varied, and have a potentially wide scope from death certification through clinical illness and from laboratory reports to social factors. The interpretation of surveillance data is a skill which must also take into account the strengths and weaknesses of the source data. Informed feedback is an essential final step to action.